The use of the genetic algorithm to estimate the parameters function of the hypoexponential distribution by simulation - Mohammed, Salam Jasim (Journal of Economics and Administrative Sciences, 2021)
In this research, the focus was placed on estimating the parameters of the Hypoexponential distribution function using the maximum likelihood method and genetic algorithm. More than one standard, including MSE, has been adopted for comparison by Using the simulation method